A (t, n) threshold protocol of semi-quantum secret sharing based on single particles - Zhou, Ziyi; Wang, Yifei; Dou, Zhao; Li, Jian; Chen, Xiubo; Li, Lixiang (Frontiers in Physics, 2023)
Semi-quantum secret sharing is an important research issue in quantum cryptography. In this paper, we propose a (t, n) threshold semi-quantum secret sharing protocol, which combines the practicality of semi-quantum secret sharing protocols and the flexibility of (t, n) threshold quantum secret sharing protocols. Participants prepare and transmit single particles in a circular way, and then any t out of n participants can recover the secret according to Shamir’s secret sharing scheme. As quantum resources, single particles are easy to prepare. Furthermore, classical participants only need to possess the capability to prepare and insert particles. The security analysis shows our protocol has security against most attacks. Except decoy particles, all particles are useful to carry the secret message, so the efficiency of the proposed protocol can achieve 100%.